Study on role of magnesium Sulphate as a Tocolytic agent in preventing preterm labour - Lipi, Lutfa Begum; Begum, Nasima; Alam, Ummum Khair; Jahan, Rounak; Rahman, Mohammed Mizanur; Rumana, Ratu (Journal of Dhaka Medical College, 2015)
A prospective study was done to assess the effectiveness of magnesium sulphate therapy given to women in preterm labour with the aim preventing preterm birth and its sequel. The place of study was the Department of Obstetrics & Gynecology, Sir Salimullah Medical College & Mitford Hospital, Dhaka. The study population were all primi and multigravida with preterm labour admitted in the above mentioned hospital, from January to December, 2009. Gestational age, maternal pulse, blood pressure, temperature, urine output, respiratory rate, uterine contractions, cervical effacement, dilatation and amniotic membrane status were elicited. Data were collected by questionnaire and analyzed with SPSS version 12.0. The results showed that magnesium sulphate injection is an effective method for tocolysis and appears to be safe for the mother and fetus and is a promising option for the treatment of preterm labour in a low resourced setting. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21538 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 179-184